Risk of stillbirth in pregnant women with obesity in the United Kingdom. Issue 5 (September 2016) - Jacob, L.; Kostev, K.; Kalder, M.
Summary: Background: The stillbirth rate in the United Kingdom (UK) is approximately 3.5–4 per 1000 births. The country has one of the highest stillbirth rates in Europe, constituting a substantial portion of the UK perinatal death rate, which was estimated in 2013 at 6.7 deaths per 1000 births. Aim: To analyse the risk of stillbirth in pregnant women with and without increased BMI in the United Kingdom (UK). Design and setting: Retrospective study based on Disease Analyzer database (IMS Health). Method: A total of 44, 060 pregnant women with or without an increased BMI who gave birth to a single child were examined using a Disease Analyzer database that included 102 general practices. Selected patients were observed for a period of at least 10 months between January 1994 and December 2013. Standard BMI ranges were considered: 18.5–24.9 (normal weight), 25–29.9 (overweight), 30–39.9 (class I and class II obese), 40–49.9 (class III) and over 50 (class IV). Multivariate logistic models were used to estimate the relationship between increasing BMI and the rate of stillbirth adjusted for demographic data and co-morbidities. Results: BMI increase was associated with an increase in stillbirth OR, from 1.37 (95% CI: 1.02–1.85) in the overweight group to 5.04 (95% CI: 1.79–14.07) in the group of pregnant women with a BMI higher than or equal to 50. Conclusions: Pregnant women with obesity and even moderate overweight exhibit an increased risk of stillbirth in UK primary care practices over 20 years.